The potential of ultrasound in cardiac pacing and rhythm modulation. (1st September 2016) - Kohut, Andrew R.; Vecchio, Christopher; Adam, Dan; Lewin, Peter A.
ABSTRACT: Introduction : This review examines the potential for ultrasound to induce or otherwise influence cardiac pacing and rhythm modulation. Areas covered : Of particular interest is the possibility of developing new, truly non-invasive, nonpharmacological, acute and chronic, ultrasound-based arrhythmia treatments. Such approaches would not depend upon implanted or indwelling devices of any kind and would use ultrasound at diagnostic exposure levels (so as not to harm the heart or surrounding tissues). It is known that ultrasound can cause cardiomyocyte depolarization and a variety of underlying mechanisms have been proposed. Expert commentary : Questions still remain regarding the effect of exposure parameters and work will also be necessary to identify the optimal target regions within the heart if ultrasound energy is to be used to induce safe and reliable pacing in a clinical setting.